Retinoic Acid Inhibits Tumor-Associated Mesenchymal Stromal Cell Transformation in Melanoma - Lou, Qi; Zhao, Minyi; Xu, Quanhui; Xie, Siyu; Liang, Yingying; Chen, Jian; Yuan, Lisha; Wang, Lingling; Jiang, Linjia; Mou, Lisha; Lin, Dongjun; Zhao, Meng (Frontiers in Cell and Developmental Biology, 2021)
Bone marrow mesenchymal stem/stromal cells (BMSCs) can be transformed into tumor-associated MSCs (TA-MSCs) within the tumor microenvironment to facilitate tumor progression. However, the underline mechanism and potential therapeutic strategy remain unclear. Here, we explored that interleukin 17 (IL-17) cooperating with IFNγ transforms BMSCs into TA-MSCs, which promotes tumor progression by recruiting macrophages/monocytes and myeloid-derived suppressor cells (MDSCs) in murine melanoma. IL-17 and IFNγ transformed TA-MSCs have high expression levels of myelocyte-recruiting chemokines (CCL2, CCL5, CCL7, and CCL20) mediated by activated NF-κB signaling pathway. Furthermore, retinoic acid inhibits NF-κB signaling, decreases chemokine expression, and suppresses the tumor-promoting function of transformed TA-MSCs by prohibiting the recruitment of macrophages/monocytes and MDSCs in the tumor microenvironment. Overall, our findings demonstrate that IL-17 collaborating with IFNγ to induce TA-MSC transformation, which can be targeted by RA for melanoma treatment.